Infantile Acute Conjunctivitis Induced by β-Lactamase–Positive Amoxicillin–Clavulanate–Resistant Strain of Haemophilus influenzae: A Report of Three Cases - Inada, Noriko (Eye Contact Lens, 2019)
This study is a retrospectively recruited case series. We report three infants with acute conjunctivitis induced by β-lactamase–positive, ampicillin/clavulanic acid-resistant strains of Haemophilus influenzae (BLPACR). Patients with BLPACR-positive cultures were recruited from among 5,107 patients with inflammatory diseases of the ocular surface who underwent examinations, including bacterial culturing of conjunctival sac or corneal scrapings, between 2000 and 2015. Three BLPACR-positive patients were recruited, including a 10-month-old boy, a 4-month-old girl, and a 7-month-old girl. All three demonstrated BLPACR conjunctivitis. The clinical findings in these patients included fever, mucopurulent discharge, lid swelling, and conjunctival hyperemia. Samples of conjunctival swabs were obtained from all three infants, and BLPACR was isolated from all these conjunctival swabs. Antimicrobial susceptibility testing showed sensitivity to levofloxacin and resistance to ampicillin, cefaclor, and clarithromycin. We conclude that in infantile BLPACR conjunctivitis, simultaneous investigation for the determination of causative organism and antibiotic susceptibility testing are crucial aspects of the medical treatment.